Effects of Ralgro® implants from birth to slaughter on carcass and meat traits of young bulls - Gray, D.G.; Unruh, John A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Implanting young bulls with Ralgro® from birth to slaughter maintained performance similar to nonimplanted bulls, increased quality grade and carcass fatness, delayed carcass masculinity development, decreased hide weight and thickness, and improved some meat palatability traits. Our results indicate that implanting young bulls with Ralgro® from birth to slaughter improves the traits cited most often by beef packers as reasons for discriminating against young bulls for meat production.
Keywords: Beef; Implants; Carcass; Meat traits